GENE MUTATIONS IN BETA THALASSEMIA PATIENTS AT QUANG NINH OBSTETRICS AND PEDIATRICS HOSPITAL (Vietnam Journal of Community Medicine, 2022)
Objectives: This study aimed to identify some frequent Beta - thalassemia mutations in QuangNinh Obstetrics and Pediatrics hospital in 2021.Methods: The cross-sectional descriptive study included 39 children with Beta - thalassemia atand under the age of 15 years old.Results: Arcording to the results, 8 Beta-thalassemia mutations were detected. In total, 86.4%of the patients had one among 8 common Beta-thalassemia mutations in the North of Vietnam.There were 4 most frequent Beta-thalassemia mutations: cd17 (AAG-TAG), cd41/42 (-TCTT),cd26 (GAG-AGG) and cd71/72 (+A), which accouting for 86.4% detected mutations. In addition,4 compound mutations were observed: cd41 – cd42, cd41/42 – cd17, cd17-cd17 , cd17 – cd26which were classified into 4 main genotypes: β0 β0, β+ β+, β0 β+, β0 βE.Conclusion: The study identified the genetic mutations by using PCR method which might notbe able to detect some rare mutations in Beta-thalassemia patients. To avoid this, it is necessary tocombined more molecular analysis techniques.
Keywords: Children, Beta-thalassemia, Quang Ninh Obstetrics and Pediatrics hospital.